Responding to increased aridity: Evidence for range shifts in lizards across a 50-year time span in Joshua Tree National Park. (August 2020) - Barrows, Cameron W.; Sweet, Lynn C.; Rangitsch, Jeffery; Lalumiere, Kristen; Green, Tyler; Heacox, Scott; Davis, Melanie; Vamstad, Michael; Heintz, James; Rodgers, Jane E.
Abstract: North American deserts are warming and becoming more arid at rates that exceed global averages. Desert lizard populations are typically dependent on plant and arthropod food resources catalyzed by variations in aridity. Shifts in those lizard distributions coincident with increasing aridity therefore present an opportunity to document responses to modern climate change as it is happening. Here, we analyzed observation frequencies across an elevation gradient for seven lizard species, comparing a historical dataset (1958–1972) to recent observations (2014–2018) within Joshua Tree National Park, a landscape straddling the Mojave and Colorado Deserts in southern California. Phrynosoma platyrhinos, Aspidoscelis tigris, and Callisaurus draconoides, now appear to occupy new, higher elevation habitats compared to the historical baseline. Except for Sceloporus occidentalis, observation records for each species indicated shifts toward the upper elevations of their ranges. Observations for Uta stansburiana, C. draconoides and A. tigris each shifted their mean elevation upslope ≥10%. Phrynosoma platyrhinos and A. tigris shifted their maximum elevations by ≥15%. To assess whether those elevation shifts could then be corroborated with independent data, we compared the historic-recent observation data with plot-based surveys where we measured lizard densities varying with elevation and rainfall levels from 2014 to 2019. Those historical-recent shifts paralleled changes in lizard densities over the same elevation gradient, with statistical support for the upslope shifts identified for U. stansburiana, A. tigris and, S. magister . Additionally, despite increases in warming and aridity, we found species-specific elevations where local conditions are supporting higher population densities and that may represent climate refugia.